Causal Analysis of Inflation and Interest Rates in Post-COVID Indonesia (2020.1-2024.9) - Putri, Kharmelia; Maryam, Siti; Bachtiar, Arief (Gorontalo State University, 2025)
This study, titled “Causality Analysis of Inflation and Interest Rates in Indonesia Post-COVID-19 (2020.1-2024.9),” aims to examine the long-term equilibrium between inflation and interest rate variables and to explore their causal relationship during the post-pandemic period. The research utilizes secondary data in the form of monthly time series from January 2020 to September 2024, sourced from Bank Indonesia publications. The cointegration test results indicate no long-term equilibrium between inflation and interest rates. However, the Granger causality test reveals a bidirectional relationship between the two variables, meaning that inflation influences interest rates, and interest rates, in turn, affect inflation. Specifically, high inflation tends to drive up interest rates, while an increase in interest rates can suppress inflation. Therefore, Bank Indonesia must carefully consider this dynamic. Any changes in interest rates should not only be assessed based on their impact on inflation but also on how inflation itself may influence future interest rate decisions. This creates a complex cycle of interdependence between the two variables, particularly in the context of a volatile economic environment. This study provides insights into the interaction of these key economic indicators within the framework of Indonesia’s post-pandemic economic recovery.